Novel strategy for microalgae cell disruption and wet lipid extraction by employing electro-Fenton process with sacrificial steel anode. (January 2022) - Sandani, Wanniarachchige Paramitha; Premaratne, Malith; Ariyadasa, Thilini U.; Premachandra, Jagath Kumara
Graphical abstract: Highlights: Chlorella homosphaera cells were disrupted using electro-Fenton process (EFP). A sacrificial steel anode was used as the source of Fe 2+ for the Fenton reaction. Response surface methodology (RSM) was utilized to optimize EFP. EFP significantly improved the lipid yield (19.99 ± 1.33%) from wet biomass. Biodiesel synthesized from lipids obtained via EFP show favorable properties. Abstract: Electro-Fenton process (EFP) was studied as a potential cell disruption technique for recovery of lipids from wet biomass of the microalga Chlorella homosphaera . A novel approach of electrochemical dissolution of a sacrificial steel anode was used to provide Fe 2+ required to initiate EFP and microalgae cell disruption. Response surface methodology (RSM) was employed to optimize the process parameters and maximize the lipid yield of EFP. The RSM model (R 2  = 90.66%, Adj.R 2  = 87.71%) showed that a maximum lipid yield of 18.29% could be obtained at 40 min reaction time and 4.38 g/L biomass concentration. Experimental validation resulted in a lipid yield of 19.99 ± 1.33%, which was significantly higher than wet lipid extraction without cell disruption. However, the lipid yield of EFP should be further improved to achieve comparable results to mechanical cell disruption methods. Nonetheless, biodiesel synthesized from lipids obtained via EFP conformed to the ASTM D6751-12 standard.